2021
DOI: 10.1364/ao.423191
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of the DKDP-based high-energy optical parametric chirped pulse amplifier for a 100  PW class laser

Abstract: An optical parametric chirped pulse amplifier (OPCPA) based on a large-aperture DKDP crystal and pumped by a 10 kJ level Nd:glass laser can serve as the final amplifier for a 100 PW level laser. A comprehensive numerical investigation on such a high-energy OPCPA is presented in this work. The effects on the efficiency–bandwidth product induced by the deuteration level, absorption loss, temperature variation, and optimization of zero-phase-mismatch wavelength (ZPMW) are analyzed in detail. Based on the analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…[10], the dependence of the refractive index of this crystal on the wave frequency (the Sellmeier formula) was determined for an arbitrary degree of deuteration and it was found that, when pumped by the second harmonic of a neodymium laser at the central wavelength of an amplified pulse of 910 nm, ultra-wideband phase matching exists. Further studies [30,[52][53][54][55][56] confirmed these results and showed the prospectivity of using a DKDP crystal for broadband OPCPA. In combination with the ability to grow a crystal with an aperture of tens of centimeters, this provides a unique opportunity to transfer energy from a narrow-band neodymium laser pulse to a broadband chirped pulse that can be compressed down to 10-20 fs.…”
Section: The Intermediate Opcpasupporting
confidence: 52%
See 1 more Smart Citation
“…[10], the dependence of the refractive index of this crystal on the wave frequency (the Sellmeier formula) was determined for an arbitrary degree of deuteration and it was found that, when pumped by the second harmonic of a neodymium laser at the central wavelength of an amplified pulse of 910 nm, ultra-wideband phase matching exists. Further studies [30,[52][53][54][55][56] confirmed these results and showed the prospectivity of using a DKDP crystal for broadband OPCPA. In combination with the ability to grow a crystal with an aperture of tens of centimeters, this provides a unique opportunity to transfer energy from a narrow-band neodymium laser pulse to a broadband chirped pulse that can be compressed down to 10-20 fs.…”
Section: The Intermediate Opcpasupporting
confidence: 52%
“…In the intermediate amplifier, the beam diameter is 10 cm and, in principle, a lithium triborate (LBO) crystal [ 58 ] can be used, but the gain band in it is shifted towards short wavelengths [ 5 ] . As the degree of deuteration of the DKDP crystal decreases, the center of the gain band shifts to the long wavelength region, closer to degenerate phase matching; the band width increases, but the idler wave absorption also increases [ 55 , 56 ] . For the required spectral width of 150 nm (see Section 2.6), the deuteration degree of 80% seems to be optimal.…”
Section: Exawatt Center For Extreme Light Studies Lasermentioning
confidence: 99%
“…Simulated by a twodimensional (2D) particle-in-cell (PIC) code ELMIS [15], composite targets were shown be able to produce ion beams with an energy spread as low as and Fe 24+ with energy up to at laser intensities of [16]. Simulated results using a 2D PIC code KLAP2D [17,18] showed that a laser of can turn out a singleenergy Fe 24+ beam with a peak energy of [19], and 2D PIC simulations with the EPOCH code [20] showed an acceleration ability with Au up to , which has been confirmed in experiments [21].…”
Section: Introductionmentioning
confidence: 63%
“…) [21], as shown in figure 1(a). The tendencies of all Au ion energy spectra are approximately same.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Furthermore, the computational requirements are exponentially increasing in case of large beam sizes and longer than 10 ps pulse durations. However, even with 2D models, which take into account the temporal shape of the pulse and the interaction distance (t, z) [59,60] or those which neglect some features, for example dispersion [61], can provide useful information. The effectiveness of 4D models (x, y, t, z) during the design of OPCPA systems operating in the few picosecond temporal range, has been proven by many authors [62][63][64][65].…”
Section: Motivation and Aim Of This Workmentioning
confidence: 99%